Análise numérica da flambagem do montante de alma devida ao cisalhamento em vigas de aço celulares - Hugo Cesar Vieira (2014)
Currently, the use of cellular beams has been intensely increasing, due to their flexible geometry and to the fact that they provide, in several situations, a more economical design. Thus, for an efficient utilization, the knowledge of their behaviour is extremely important. However, it was observed that there are few works related to cellular beams, especially with regard to their collapse modes. In this context, one of the most complex collapse modes is the web-post buckling by compression or by shear. The spacing between the openings, the web slenderness and the opening diameter are some parameters that influence the phenomenon, but the knowledge of their behaviour is still unclear. This project aims at evaluating, by nonlinear Finite Element Method (FEM) analysis, the behavior of the cellular steel beams, according to the web-post buckling due to shear. In addition, it targets on studying and examining existing analytical formulations and, if necessary, proposing new procedures, considering the range variation of the slenderness of the web rolled parallel faces I profiles (W series) manufactured in Brazil. For this, numerical models were developed, taking geometric and material nonlinearities into account. Available results in the literature were used for validation and calibration of these models. It was observed that the web-post buckling by shear occurs predominantly when the spacing and diameter of the openings ratio is between 1.2 and 1.4. Additionally, considering the good approximation of the obtained results, the resistance capacity is based on Lawsons et al. (2002) methodology. However, some differences were observed especially when the diameter of the openings and the total height of the cellular beam cross section ratio (D0/dg) and the step and the diameter of the openings ratio (p/D0) are reduced. Furthermore, it was observed that Lawsons et al. (2002) method doesnt consider properly the beams with a small the distance between the faces of the openings. Based on these findings, two adjustment factors were added to Lawsons et al. (2002) method, so that its results could approximate the numeral results got in this work.